2019
DOI: 10.1242/jcs.224766
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomes control mitochondrial dynamics and the mitochondrion-dependent apoptosis pathway

Abstract: Peroxisomes cooperate with mitochondria in the performance of cellular metabolic functions, such as fatty acid oxidation and the maintenance of redox homeostasis. However, whether peroxisomes also regulate mitochondrial fission-fusion dynamics or mitochondriondependent apoptosis remained unclear. We now show that genetic ablation of the peroxins Pex3 or Pex5, which are essential for peroxisome biogenesis, results in mitochondrial fragmentation in mouse embryonic fibroblasts (MEFs) in a manner dependent on Drp1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…It has been shown that this is a more complex process, including the development of pre-peroxisomes originated from mitochondria, which fuse with endoplasmic vesicles from the ER for maturation by a PEX3 cycling process (Sugiura et al, 2017). On the other hand, the specific loss of hepatic peroxisomes, e.g., in liver-specific PEX5 –/– KO mice, leads to mitochondrial malformation or function in the liver but not in other physiological relevant tissues (Dirkx et al, 2005; Shinde et al, 2018; Tanaka et al, 2019). This indicates that the generation of peroxisomes is functionally closely related to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that this is a more complex process, including the development of pre-peroxisomes originated from mitochondria, which fuse with endoplasmic vesicles from the ER for maturation by a PEX3 cycling process (Sugiura et al, 2017). On the other hand, the specific loss of hepatic peroxisomes, e.g., in liver-specific PEX5 –/– KO mice, leads to mitochondrial malformation or function in the liver but not in other physiological relevant tissues (Dirkx et al, 2005; Shinde et al, 2018; Tanaka et al, 2019). This indicates that the generation of peroxisomes is functionally closely related to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…This process involves the budding of endoplasmatic reticulum (ER) and the import of cytosolically translated proteins, so that the unambiguous assignment of proteins to distinct organelle structure becomes more and more difficult (van der Zand et al, 2012; Schrader et al, 2013; Tabak et al, 2013). Moreover, mitochondria are also integrated in this flowing process (Dirkx et al, 2005; Tanaka et al, 2019). In addition, the close proximity of peroxisomes to lipid droplets led to an interaction of cellular structures to transfer lipids for degradation, but also the bilateral process is possible to exchange specific lipids (Binns et al, 2006; Bartz et al, 2007; Pu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Physical contacts between peroxisomes and mitochondria have been well studied, 43 , 44 and more importantly, a recent study indicated that mitochondrial fission could be regulated by peroxisomes. 45 Based on these notions, it is possible that TMEM135 functions in peroxisomes and its perturbation may, in turn, affect mitochondrial dynamics. Alternatively, TMEM135 may have multiple molecular functions, and RPE phenotypes we have observed may be in part caused by a defect in a different function/pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated that excessive ROS production by peroxisomes led to mitochondria-induced cell death in Pex19p-deficient human fibroblasts and that this process may be countered by targeted overexpression of select antioxidant enzymes: peroxisomal glutathione S-transferase Kappa 1, SOD1, and mitochondrial catalase (Wang et al, 2013). Similarly, Peeters et al demonstrated disruption of peroxisome biogenesis in hepatocyte-selective Pex5 knockout mice to damage MIM, deplete mtDNA, reduce or incomplete respiratory chain complexes I, III, and V, increase oxidative stress, increase mitochondrial membranes permeability and fluidity, and increase mitochondrial biogenesis (Peeters et al, 2015;Tanaka et al, 2019). Both peroxisome and mitochondrial dysfunction and dysregulated ROS balance is important in the occurrence of age-related disease (Cipolla and Lodhi, 2017).…”
Section: Importance Of Peroxisomal Health On Mitochondrial Integritymentioning
confidence: 99%